Navigating adulthood: Exploring the transition needs of adolescents and young adults affected by Duchenne or Becker muscular dystrophy - Sharon Barak; Shirley Ackerman Laufer; Michal Gudinsky Elyashiv; Sharon Rubinstein-Shatz; Rama Davidson; Tali Kaplan (PLoS ONE, 2025)
For individuals with Duchenne or Becker muscular dystrophy (DMD and BMD, respectively), transitioning to adulthood presents significant challenges. Although considerable attention has been given to facilitating medical transitions due to the complexity of these conditions, less focus has been placed on other aspects of the transition, such as achieving independence. This study assessed the transition needs of people with DMD or BMD, exploring various domains including health, education, employment, living arrangements, transportation, daily activities, and independent personal life. Men with DMD or BMD participated in this cross-sectional study. Transition to adulthood was assessed using Transition Readiness Assessment for Young Adults with DMD. The questionnaire evaluates transitions in health care, education and employment, housing and transportation, activities of daily living, and independent life and autonomy. Factors associated with and predicting transition to adulthood were evaluated using Spearman’s correlations and multiple regression analysis. Forty-two people with DMD or BMD (mean age: 24.3±5.3) participated in this study. The transition domains in which most participants needed help were education and employment (52.5%) and activities of daily living (57.0%). Transition needs that stood out included palliative care (66.6%), employment and education support (76.1%), social worker consultation for housing assistance (76.1%), and assistive device consultation (64.2%). Mobility and breathing function did not correlate with transition level. Number of siblings positively correlated with and predicted most transition domains. Older age predicted only education and employment status. In conclusion, the analysis showed that the most problematic transition domains among people with DMD or BMD were activities of daily living and education and employment. In most transition domains, help needed did not decrease with age and was not affected by function. However, adolescents and adults with more siblings typically reported being more ready to transit to adult life.